(untitled) (Global Journal of Management and Business Research, 2023)
ABSTRACT In the North region of Brazil the economic and social significance of the artisanal a a whisking activity cannot be contested a reality that instigates research In this context the objective of studying and better knowing the activity of the scout under the precepts of the Institutionalist Theory emerged In order to reach the established purpose an Exploratory Research type was adopted with a bias of Integrative Review of the theoretical framework underlying the Institutionalist Theory As a result it is understood that it is possible to infer that the Institutionalist Theory and its evolution makes it possible to homogeneously support not only studies focused on objects in the form of companies enterprises organizations and correlates thus generating a framework and as a consequence common deliverables for each object Keywords Institutionalist Theory Integrative Review Handmade Acai Whisk